De geest van Munster. De botsende economische en commerciële belangen van België en Nederland en de invloed op de wederzijdse beeldvorming (1830-1940) - Waele, M. de (BMGN - Low Countries Historical Review, 2000)
The spirit of Munster. The conflicting economic and commercial interests of Belgium and the Netherlands and the influence this had on their perceptions of one another (1830-1940)The treaty of Munster, which at the request of the Dutch officially decided the closure of the Scheldt in 1648, cast a long shadow. When the separation between Belgium and Holland was settled in 1839, the terms regarding the statute of the Scheldt and the waterways between the Scheldt, the Meuse and the Rhine were perceived as distinctly disadvantageous in Belgium and its main port Antwerp. The intransigence of the Dutch during later rounds of talks confirmed their reputation for greed and meanness. More than one Belgian diplomat remained convinced that the notorious Munster spirit was still very much alive. The outbreak of the first World War put the problem of the waterways in a different bilateral and international perspective. Several leading Belgian politicians and diplomats aspired to incorporate the Dutch territories of Zeeland Flanders and Limburg. Although these claims were mainly inspired by strategic motives, those advocating them realised that this would allow Belgium to settle the waterways problem in its favour once and for all. Other policymakers, although opposed to territorial gains, hoped that the war would result in a favourable settlement of this tricky problem. However, the Belgians' territorial claims and their aggressive nationalist campaign so angered the Dutch that during the Paris negotiations in 1919 they were more intransigent than ever. This round of talks reached a deadlock in the spring of 1920, and an agreement was not found before 1940.